Origin of the Anomalous Subantarctic Mantle: Message from the Kerguelen Large Igneous Province and Macquarie Ridge Complex - Jiang, Qiang (Curtin University, 2021)
This thesis uses 40Ar/39Ar geochronology, geochemical analyses, and a series of other techniques to study the age and composition of basaltic rocks from the Kerguelen large igneous province and Macquarie Ridge Complex in the Subantarctic region. The results provided new insights into the tectonic, geochemical, and environmental significance of these exceptional magmatism, as well as the chemical heterogeneity and geodynamics of the Subantarctic mantle.